2010
DOI: 10.2147/ceg.s9334
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory bowel diseases and the general practitioner’s role in a region of Central Italy

Abstract: Background:Inflammatory bowel diseases (IBD) are a serious burden for both patients and health care providers because of the young age at which they occur and their chronic course.Aim:The purpose of this study was to assess how general practitioners (GPs) in the area of Camerino-Matelica, Marche (Central Italy) manage their patients with IBD.Materials and methods:Before providing an educational course about IBD to GPs, we administered a simple questionnaire containing 10 multiple-choice questions, allowing for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…These weaknesses can be overcome with the active involvement of the PCP, who will contribute significantly to the continuous, coordinated, and holistic health care for patients with IBD. This is supported by available data showing that satisfaction with the primary physician did not depend on physician type (for example, GE versus general practitioner) 81,82. However, it should be emphasized that data concerning the degree of involvement of PCPs in management of IBD patients are limited.…”
Section: The Role Of Pcps In Early Diagnosis and Management Of Patienmentioning
confidence: 74%
“…These weaknesses can be overcome with the active involvement of the PCP, who will contribute significantly to the continuous, coordinated, and holistic health care for patients with IBD. This is supported by available data showing that satisfaction with the primary physician did not depend on physician type (for example, GE versus general practitioner) 81,82. However, it should be emphasized that data concerning the degree of involvement of PCPs in management of IBD patients are limited.…”
Section: The Role Of Pcps In Early Diagnosis and Management Of Patienmentioning
confidence: 74%
“…We recently performed a systematic review that documented a paucity of UC educational tools and/or guidelines for primary healthcare practitioners and an absence of action plans with individualised treatment plans for UC. This is despite two separate surveys reporting that 70% of general practitioners (GP) would value such clinical support tools and contrasts with chronic diseases such as asthma, congestive cardiac failure and diabetes where such tools are readily found, and additionally, at least for asthma, action plans are also easily discovered …”
Section: Introductionmentioning
confidence: 99%
“…also reported that 71.8% of 39 GPs working in the Marche region of Central Italy required better instructions when it came to IBD cases. [17] Theoretically, if PHC physician's knowledge and experience with IBD is insufficient, suboptimal management of IBD would occur, which may lead to misidentification of flares, inappropriate use of corticosteroids, overuse of aminosalicylates, or delay in delivering appropriate interventions. [15] Since IBD is no longer considered a rare disease, providing IBD-centered education for PHC physicians could aid in avoiding future morbidity of IBD by early referral and management.…”
Section: Discussionmentioning
confidence: 99%